miR-309a is a regulator of ovarian development in the oriental fruit fly Bactrocera dorsalis. - Qiang Zhang; Wei Dou; Clauvis Nji Tizi Taning; Shan-Shan Yu; Guo-Rui Yuan; Feng Shang; Guy Smagghe; Jin-Jun Wang (PLoS Genetics, 2022)
Fecundity is arguably one of the most important life history traits, as it is closely tied to fitness. Most arthropods are recognized for their extreme reproductive capacity. For example, a single female of the oriental fruit fly Bactrocera dorsalis, a highly invasive species that is one of the most destructive agricultural pests worldwide, can lay more than 3000 eggs during its life span. The ovary is crucial for insect reproduction and its development requires further investigation at the molecular level. We report here that miR-309a is a regulator of ovarian development in B. dorsalis. Our bioinformatics and molecular studies have revealed that miR-309a binds the transcription factor pannier (GATA-binding factor A/pnr), and this activates yolk vitellogenin 2 (Vg 2) and vitellogenin receptor (VgR) advancing ovarian development. We further show that miR-309a is under the control of juvenile hormone (JH) and independent from 20-hydroxyecdysone. Thus, we identified a JH-controlled miR-309a/pnr axis that regulates Vg2 and VgR to control the ovarian development. This study has further enhanced our understanding of molecular mechanisms governing ovarian development and insect reproduction. It provides a background for identifying targets for controlling important Dipteran pests.